Missed Exams and Lost Opportunities: Who Could Gain From Expanded College Admission Testing? - Emily E. Cook; Sarah Turner (SAGE Publishing, 2019)
When students with the capacity to succeed in a 4-year college do not take a college admission test, this represents a potential loss of opportunity for students and colleges alike. However, the costs of testing-both pecuniary and nonpecuniary-may exceed the benefits for students who lack the interest in or qualifications for college attendance. In states like Virginia, access to admission tests varies markedly with district and family circumstances. We estimate that universal testing in Virginia could increase the number of high school graduates with test scores competitive for admission at broad-access universities in the state by as much as 40%-and at the most selective institutions by nearly 20%-with larger increases for low-income students. Alternative policies that encourage testing among students with strong demonstrated academic performance could realize nearly these increases without generating testing costs for students who are unlikely to attend a 4-year college.